The inflammasome pathway in stable COPD and acute exacerbations - Rosa Faner (ERJ Open Research, 2016)
Chronic obstructive pulmonary disease (COPD) is characterised by pulmonary and systemic inflammation that bursts during exacerbations of the disease (ECOPD). The NLRP3 inflammasome is a key regulatory molecule of the inflammatory response. Its role in COPD is unclear. We investigated the NLRP3 inflammasome status in: 1) lung tissue samples from 38 patients with stable COPD, 15 smokers with normal spirometry and 14 never-smokers; and 2) sputum and plasma samples from 56 ECOPD patients, of whom 41 could be reassessed at clinical recovery. We observed that: 1) in lung tissue samples of stable COPD patients, NLRP3 and interleukin (IL)-1β mRNA were upregulated, but both caspase-1 and ASC were mostly in inactive form, and 2) during infectious ECOPD, caspase-1, oligomeric ASC and associated cytokines (IL-1β, IL-18) were significantly increased in sputum compared with clinical recovery. The NLRP3 inflammasome is primed, but not activated, in the lungs of clinically stable COPD patients. Inflammasome activation occurs during infectious ECOPD. The results of this study suggest that the inflammasome participates in the inflammatory burst of infectious ECOPD.